Principal-Led Clinical Supervision in Indonesian Schools: Advancing Teacher Professional Development for SDG 4 - Akhmad Mundir; Andi Kristanto; Amrozi Khamidi (Journal of Current Studies in SDGs, 2026)
Objective: To investigate the impact of principals' clinical supervision on teachers' pedagogical competence within the cultural context of Indonesian schools. Clinical supervision has been shown to promote reflective practice. However, its implementation in Indonesia is often a formality to meet government-set management standards, rather than a means of developing teachers' competencies. Method: To use a convergent mixed-methods research design and involved eighty-nine teachers and six principals from six elementary and junior high schools in Jombang, East Java. Quantitative data, derived from pre- and post supervision. Result: After clinical supervision, showed statistically significant improvements in teachers' pedagogical skills. The most substantial improvements were seen in teachers' lesson planning and evaluation. Qualitatively, thematic analysis found that teachers initially experienced "fear of exposure" and professional shame during the supervision process. Affective resistance evolved into a journey of collaborative discovery as the supervision progressed. These findings highlight that the effectiveness of transforming teachers' pedagogical competence is embedded in the school's organizational culture. Novelty:  Schools that demonstrated high levels of interpersonal trust between teachers and principals performed better than schools governed by rigid organizational norms. This study concludes that for clinical supervision to be truly effective in Indonesia, it must be reimagined as a culturally sensitive and mandated dialogue, not simply an administrative requirement. The implications suggest that educational policymakers should shift their focus toward coaching-based leadership training, emphasizing psychological safety and relational trust as catalysts for professional growth and teaching quality.